Applying the concept map of audio-visual learning in improving science learning outcomes on dynamic electricity - Titin Rahmayanti Rambe; Dinesh Elango; Wina Mariana Parinduri; Renni Ramadhani Lubis; Dyan Wulan Sari HS (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study is motivated by ninth-grade students' low science learning outcomes at SMP Negeri 2 Labuhan Deli. The study aimed to improve students' science learning outcomes using the concept map method. The research instruments used in this study were observation and test questions. The data analysis shows an improvement in students' learning outcomes. In the pre-test on dynamic electricity, only seven students (33.3%) achieved a score of 70 or above, while 14 students (66.6%) did not. The average pre-test score was 62. After being taught using the concept map method, in the post-test, 18 students (85.7%) were deemed to have achieved mastery if their scores were equal to or above the minimum passing grade of 70, while three students (14.3%) did not achieve mastery. Thus, applying the concept map learning method to dynamic electricity material is quite effective because it can improve student learning outcomes. The N-gain test data calculation also yielded an N-Gain score of 46.01%, which falls under the Effective N-Gain Interpretation Category. -Gain Interpretation Category, where a score of 46–75 is interpreted as sufficiently effective in improving student learning outcomes.